Chinese burdens and trends of diabetic retinopathy 1990–2021 and 15 years forecast: results from the Global Burden of Disease Study 2021 - Jiang, Chun; He, Xiuhui; Zhu, Yingying; Tao, Liming (Frontiers in Endocrinology, 2025)
ObjectivesTo assess the Chinese burden of diabetic retinopathy (DR) between 1990 and 2021, considering variations by year, age, and gender, as well as to forecast the trends over the next 15 years.MethodsWe evaluated the burden of DR in China based on data from the GBD 2021, examining prevalence, years lived with disability (YLDs), age-standardized YLDs rates (ASYR), and age-standardized prevalence rates (ASPR) over the period 1990 to 2021. Furthermore, we utilized joinpoint analysis and the Bayesian age-period-cohort model to explore the epidemiological patterns of the disease and forecast its impact for the years 2022 to 2036.ResultsIn 2021, the number of YLDs and prevalence attributed to DR were 86,317 (95% UI: 56,595 to 125,565) and 1.37 million (95% UI: 1.04 to 1.78), respectively. Over the period 1990 to 2021, the AAPC of ASYR and ASPR for DR rose by 0.71 (95% CI: 0.28, 1.14) and 0.43 (95% CI: 0.20, 0.66) in China. Older adults and women experienced a greater burden. Aging and demographic changes are key risk factors for DR, and future trends suggest a decrease in ASYR and ASPR.ConclusionThe Chinese burden of DR has increased during the years 1990 to 2021. Despite the anticipated decline in the burden of DR between 2022 and 2036, the importance of bolstering efforts in DR prevention and control should not be underestimated.